Development of a Quantitative Estimation of Mammographically Breast Density (Bangladesh Journal of Nuclear Medicine, 2017)
Objective: Increased mammographic breast density is a moderate independent risk factor for breast cancer. Assessment of breast density may become useful in risk assessment and prevention decisions. To evaluate the association between mammographic density and breast cancer risk, a simple observer-assisted technique called interactive thresholding was developed.Methods: For providing, a quantitative estimation of mammographically dense tissue, in this study computer assisted measurements were carried out using Adobe AIR software. For thresholding technique, software named ‘Xray Image Analyzer’ was programmed in Adobe AIR language version - Action script 3.0. runtime version- Flash player 9, AIR 1.0, and flash Lite-4. Interactive thresholding technique was applied to digitized film screen mammograms, which assesses the proportion of radio graphically dense tissue in the mammographic image representing mammographic density. The technique evaluated for 36 mammograms of 18 women who underwent referral mammography in a hospital at Dhaka city from October 2010 to October 2011.Results: The women in the selected group were in age range of 20 to 60 years, with a mean age of 44±9 and median age is 45 yrs. The technique was found to be very reliable with an intra-class correlation coefficient between observers typically R = 0.887. This technique may have a role in routine mammographic analysis for the purpose of assessing risk categories and as a tool in studies of the etiology of breast cancer, in particular for monitoring changes in breast parenchyma during potential preventive interventions. Conclusion: It is possible to use the interactive segmentation technique for other projections of the breast, such as the medio-lateral oblique view. In this case, however, it is necessary to perform a manual segmentation to remove the image of the pectoral muscle from the analysis. This technique can be employ as a tool in many clinical studies.Bangladesh J. Nuclear Med. 18(1): 16-20, January 2015